Scalable Front-End Architecture: Building for Growth and Sustainability - Tkachenko, Oleksandr; Chechet, Aleksei; Chernykh, Maksim; Bunas, Sergei; Jatkiewicz, Przemyslaw (Informatica, 2025)
The aim of the research is to develop strategies for building scalable interface architectures that ensure stability and protection of user data. The research identified the key characteristics of scalable interface architectures, such as ReactJS, GraphQL, and SSR. Within the scope of the research, principles for constructing scalable front-end architectures have been developed and described. These principles, such as modularity, componentisation, microservices architecture, adaptive and responsive design, as well as load management and scalability, data security, and fault tolerance, aim to ensure flexibility, efficiency, and user convenience across various devices and under different conditions. These principles enable the creation of architectures capable of adapting to changing requirements and scaling to ensure high performance and reliability when dealing with various types of data and workloads. The practical significance of the study is determined by the creation of a pragmatic guide for developers and architects of front-end systems who seek to create scalable applications.